Nutritional Composition, in vitro Antioxidant Activity and Artemia salina L. Lethality of Pulp and Seed of Tamarindus indica L. Extracts - Fairuz Azman, Khairunnuur; Amom, Zulkhairi; Azlan, Azrina; Mohd Moklas, Mohamad Aris; Sapari, Khairullizam; Md Shah, Zamree; Mohd Arshad, Mohd Shahidan (Nutrition Society of Malaysia, 2009)
This study was designed to examine the nutritional composition, antioxidant activity and medium lethal concentration (LC50 value) of Tamarindus indica L. pulp and seed extracts in vitro. The extraction was set at 40°C, 60°C and 100°C for 12 hours, 6 hours and 15 minutes respectively to determine the optimum extraction parameter whereas the anti-oxidant activity of the extracts was measured using iron (III) reduction (FRAP) assay. Total phenolic content (TPC) of the extracts was estimated as gallic acid equivalent by Folin-Ciocalteau method. Toxicity potential of the extract was assessed in vitro by Artemia salina lethality test both in seed and pulp samples. The results showed that tamarind seed contained a higher percentage of carbohydrate, protein, fat and energy (15%, 82%, 95% and 33.13% respectively) than the pulp. On the other hand, the pulp demonstrated a high moisture (51.1%) and ash (34.84%) content than the seed. For the mineral analysis, tamarind seed contained higher Ca and C (1.0% and 50.73% respectively) than the pulp (0.27% and 40.40% respectively). No heavy metals were detected in both samples. Seed extracted at 60°C/6 hours and 100°C/15 minutes showed the highest TPC value and were significantly different (p<0.05) than the seed extracted at 40°C/12 hours. Anti-oxidant activity is positively correlated to the TPC value of the extracts (R=0.991). The pulp and seed extracted at 100°C/15 minutes showed the highest FRAP value among its groups (216.17 ± 14.06 μmol (Fe)/g and 659.74 ± 16.40 μmol (Fe)/ g respectively). This study indicates that tamarind pulp and seed extracts possess beneficial antioxidant properties and the optimum extraction parameter is 100°C for 15 minutes. In Artemia salina lethality test, tamarind pulp caused significant mortality of the crustacean larvae with LC50 in the range of 26-28 μL/mL. Tamarind seed were not toxic to Artemia salina since the LC50 of the extracts was higher than 1000 μL/mL.